Legal Validity of Digital Contracts in Indonesian Business Transactions: A Normative Study of the Civil Code and Electronic Information and Transactions Law - Vivi Sylvia Purborini; Suryaningsih (Yayasan Sinergi Kawula Muda, 2026)
The development of digital business transactions in Indonesia has changed the way contracts are made, from written paper agreements to electronic agreements. This change raises legal questions about whether digital contracts are valid, enforceable, and able to provide legal certainty under Indonesian civil law. This article examines the validity of digital contracts based on Article 1320 of the Indonesian Civil Code and the Electronic Information and Transactions Law. Previous studies have discussed electronic contracts in e-commerce, electronic documents as evidence, and the recognition of digital agreements in Indonesian law. However, these studies have not clearly explained how each requirement of contract validity applies to digital business contracts. This article fills that gap by discussing electronic consent, legal capacity, clear contractual objects, lawful causes, authentication, and the reliability of electronic evidence. This study uses a normative legal method with statutory and conceptual approaches. The analysis shows that digital contracts are valid as long as they meet the requirements of Article 1320 of the Civil Code and are supported by the Electronic Information and Transactions Law. Even so, several legal problems remain, especially in proving consent, verifying the identity and capacity of the parties, protecting the integrity of electronic records, and handling cross-border digital transactions. This article concludes that Indonesian civil law can accommodate digital contracts, but clearer legal interpretation and better regulatory harmony are needed to strengthen legal certainty in modern business transactions.